Role for Activated Macrophages in Resistance Against Trichinella spiralis - Wing, Edward J. (1978)
To determine whether activated macrophages are important in resistance against the intestinal phase of nematode parasites, we studied Trichinella spiralis infections in mice with normal macrophages and in mice with macrophages activated by either chronic Toxoplasma gondii or acute Listeria monocytogenes infections. The peak T. spiralis adult worm burden in the intestines of normal C57BL/6 or Swiss Webster mice occurred from 6 to 14 days after infection. Subsequent expulsion of worms from the intestines occurred from 8 to 20 days after infection. C57BL/6 mice chronically infected with T. gondii and then challenged with T. spiralis larvae had significantly lower peak intestinal worm burdens (P < 0.05) than normal C57BL/6 mice similarly challenged. Swiss Webster mice infected 7 or 13 days earlier with L. monocytogenes and then challenged with T. spiralis larvae had significantly lower peak worm burdens (P < 0.01) than uninfected mice. The time of expulsion of adult worms was not affected by either infection. Swiss Webster mice infected 42 days earlier with L. monocytogenes (i.e., possessing lymphocytes sensitized to L. monocytogenes but not possessing activated macrophages) did not have a lower worm burden than uninfected mice. Serum factors (e.g., antibody) did not appear to play a role because normal mice injected with serum from L. monocytogenes-infected mice had worm burdens similar to those of mice injected with normal serum. The histopathology of intestines of mice infected with T. gondii or L. monocytogenes was the same as that of normal mice. When T. spiralis larvae were incubated with normal macrophages or macrophages from T. spiralis-infected mice in vitro for 24 h, the number of larvae with adherent T. spiralis macrophages was significantly (P < 0.005) greater than the number of larvae with adherent normal macrophages. These studies suggest a role for activated macrophages in resistance to T. spiralis.